Does the source of referral affect outcomes for paediatric testicular torsion? - Peeraully, R (Ann R Coll Surg Engl, 2019)
INTRODUCTION: This single centre study retrospectively analysed the intraoperative findings relative to source of referral for emergency scrotal explorations performed in a tertiary level paediatric surgery department. METHODS: All patients who underwent emergency scrotal exploration under the care of paediatric surgeons in our unit between April 2008 and April 2016 were identified. Clinical data were obtained from contemporaneous records. RESULTS: Over the 8-year study period, 662 boys underwent emergency scrotal exploration: 6 (1%) were internal referrals, 294 (44%) attended our emergency department (ED) directly, 271 (41%) were referred from primary care and 91 (14%) were transferred from other hospitals. Excluding procedures in neonates, testicular torsion was present in 100 cases (15%). Testicular detorsion with bilateral 3-point testicular fixation was performed in 66 (66%) and orchidectomy with contralateral fixation in 34 (34%) where the torted testis was non-viable intraoperatively. The orchidectomy rate in the presence of torsion was 23% in ED referrals (12/52), 43% in primary care referrals (12/28) and 50% for transfers (10/20). The difference in rates between ED referrals and patients transferred from other hospitals was significant (p=0.026). There was no significant difference in median age between any of the groups (p=0.10). CONCLUSIONS: Boys undergoing emergency scrotal exploration had a higher orchidectomy rate when transferred from other hospitals to our unit. This difference was statistically significant when compared with boys presenting directly to our ED. This supports advice from The Royal College of Surgeons of England for undertaking paediatric scrotal explorations in the presenting hospital when safe to do so rather than delaying the care of these patients by transferring them to a tertiary paediatric surgical unit.